the role of capital, type of product, and allocation of working hours to the income of kuta trade - Arini, Made Emi (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 10 (2022): vol.11.10. OKTOBER 2022 [3701 - 4009]DO - 10.24843/EEP.2022.v11.i10.p15, 2022)
Kuta Beach is famous for its beautiful beaches, many traders sell on Kuta Beach in hopes of increasing their income. The objectives of this study is to analyze the effect of simultaneous capital, product type and allocation of working hours on the income of traders in Kuta Beach, and to analyze the experience in moderating the influence of capital on the income of traders in Kuta Beach. The analyzing primary data of this study were using 92 samples data. The data analysis technique used is Multiple Linear Regression with moderation. The results of data analysis show that capital, type of product, and allocation of working hours simultaneously influence the income of the traders in Kuta Beach. Although the type of product has no significant effect on the income of traders on Kuta Beach, the allocation of working hours does not have a positive effect on the income of traders in Kuta Beach and a moderating experience that strengthens the relationship of influence between capital to the income of traders in Kuta Beach.